Inscribing Pharaoh’s initiation on the function of written artefacts and the process of writing in scenes of the ished tree, the coronation, and the initiation of the ancient Egyptian king - Kühne-Wespi, Carina (Written artefacts in rites of passage, 2025)
The process of writing as well as artefacts that have already been inscribed played a significant role during rituals that served to create an ancient Egyptian king and to establish his name and titulary. The paper at hand discusses mostly iconographic sources dating to the Egyptian New Kingdom (c.1550-1070 bce) that relate to the so-called ished tree scene, the coronation of the king and his introduction or initiation into specific temples. The contribution examines the use and function of written artefacts and the process of writing in such scenes by discussing a selection of relevant examples. It will be argued that the inscriptions produced during the ished tree and coronation scenes are specifically characterized as being of divine origin and one of their main functions is to define the king’s name as a manifestation of the divine.
Gesehen am 11.11.2024